Pemarkah Kohesi Leksikal dan Kohesi Gramatikal: Analisis pada Paragraf dalam Skripsi Mahasiswa Pend. Bahasa dan Sastra Indonesia - Anie Wulandari Azis (FKIP, Universitas Lakidende Unaaha, 2015)
The purpose of the study is to analyze the lexical and grammatical cohesion markers of paragraphs of in the students’ thesis introduction chapter. It was a qualitative descriptive study. The sources of data were the students’ theses of Indonesian Literature and Language Education Study Program in the yeasr 2010 and the data are all cohesion markers found in the paragraph of the students’ thesis introduction chapter. There are 30 theses consisting of 306 paragraphs. Sorting, reading, and noting are the techniques used in this research. The analysis showed that from 306 paragraphs, there are 243 lexical cohesion markers and 340 grammatical cohesion markers. Lexical cohesion markers were repetition (156), synonym (17), antonym (25), hyponym (6), correlation (19), and equivalence (18). On the other hand, grammatical cohesion markers consist of reference (52), substitution (39), ellipsis (11), conjunction (175), and pronoun (63).